Effect of peach peel on shape memory properties of polylactic acid - Eroglu, Murat (Sage Publications Ltd, 2024)
In this study, two different peach peel powders were produced using the sieving process: with fiber (filler-fiber powder) and without fiber (filler powder). To investigate the effects of the prepared powders on the shape memory properties of PLA, PLA/Filler (wt%90 PLA: wt%10 filler) and PLA/Fiber-Filler (wt%90 PLA: wt%10 Fiber-Filler) biocomposite films were prepared by the solvent casting technique. The shape memory properties of the films, such as shape fixity ratio and shape recovery ratio, were determined by the bending test. For the PLA film, the shape fixity ratio is 81 +/- 5%. When filler powders are applied, the shape fixity ratio is unaffected. However, when fiber-filler powder is added, the shape fixity ratio drops to 75 +/- 1%. The shape recovery ratio for PLA film is 50 +/- 7%. The shape recovery ratio increases to 54 +/- 4% when filler powder is added. However, the percentage of shape recovery ratio remains the same when filler-fiber powders are added. Shape memory performance can be enhanced by adding peach peel filler powder to the PLA. The peach peel filler can be considered as a cost-effective filler to improve the shape memory properties of PLA-based biocomposites. As a result, peach peel filler reinforced PLA based composite films may be possible low-cost and biodegreadable shape memory material candidates for a variety of industries like aerospace and soft robotics.
Keywords: Peach peel; polylactic acid; solvent casting technique; shape memory property